Vaccination against T‐cell epitopes of native ApoB100 reduces vascular inflammation and disease in a humanized mouse model of atherosclerosis. (13th February 2017) - Gisterå, A.; Hermansson, A.; Strodthoff, D.; Klement, M. L.; Hedin, U.; Fredrikson, G. N.; Nilsson, J.; Hansson, G. K.; Ketelhuth, D. F. J.
Abstract: Background and Objectives: The T‐cell response to low‐density lipoprotein (LDL) in the vessel wall plays a critical role in atherosclerotic plaque formation and stability. In this study, we used a new translational approach to investigate epitopes from human apolipoprotein B100 (ApoB100), the protein component of LDL, which triggers T‐cell activation. We also evaluated the potential of two selected native ApoB100 epitopes to modulate atherosclerosis in human ApoB100‐transgenic Ldlr −/− ( HuBL ) mice. Methods and Results: HuBL mice were immunized with human atherosclerotic plaque homogenate to boost cellular autoimmune response to tissue‐derived ApoB100 epitopes. In vitro challenge of splenocytes from immunized mice with a library of overlapping native peptides covering human ApoB100 revealed several sequences eliciting T‐cell proliferation. Of these sequences, peptide (P) 265 and P295 were predicted to bind several human leucocyte antigen (HLA) haplotypes and induced high levels of interferon (IFN)‐γ. Vaccination of HuBL mice with these peptides mounted a strong adaptive immune response to native ApoB100, including high levels of epitope‐specific plasma IgGs. Interestingly, P265 and P295 vaccines significantly decreased plaque size, reduced macrophage infiltration and increased IgG1 deposition in the plaques. Purified IgGs from vaccinated mice displayed anti‐inflammatory properties against macrophages in vitro, reducing their response to LPS in a dose‐dependent manner. Conclusion: We identified two specific epitopes from human native ApoB100 that trigger T‐cell activation and protect HuBL mice against atherosclerosis when used in a vaccine. Our data suggest that vaccination‐induced protective mechanisms may be mediated at least in part through specific antibody responses to LDL that inhibit macrophage activation.